An overview of the cutaneous porphyrias [version 1; referees: 2 approved] - Robert Dawe (F1000Research, 2017)
This is an overview of the cutaneous porphyrias. It is a narrative review based on the published literature and my personal experience; it is not based on a formal systematic search of the literature. The cutaneous porphyrias are a diverse group of conditions due to inherited or acquired enzyme defects in the porphyrin–haem biosynthetic pathway. All the cutaneous porphyrias can have (either as a consequence of the porphyria or as part of the cause of the porphyria) involvement of other organs as well as the skin. The single commonest cutaneous porphyria in most parts of the world is acquired porphyria cutanea tarda, which is usually due to chronic liver disease and liver iron overload. The next most common cutaneous porphyria, erythropoietic protoporphyria, is an inherited disorder in which the accumulation of bile-excreted protoporphyrin can cause gallstones and, rarely, liver disease. Some of the porphyrias that cause blistering (usually bullae) and fragility (clinically and histologically identical to porphyria cutanea tarda) can also be associated with acute neurovisceral porphyria attacks, particularly variegate porphyria and hereditary coproporphyria. Management of porphyria cutanea tarda mainly consists of visible-light photoprotection measures while awaiting the effects of treating the underlying liver disease (if possible) and treatments to reduce serum iron and porphyrin levels. In erythropoietic protoporphyria, the underlying cause can be resolved only with a bone marrow transplant (which is rarely justifiable in this condition), so management consists particularly of visible-light photoprotection and, in some countries, narrowband ultraviolet B phototherapy. Afamelanotide is a promising and newly available treatment for erythropoietic protoporphyria and has been approved in Europe since 2014.